Peran Edukasi Finansial dalam Membentuk Kesadaran Investasi Generasi Z - Putri Dini Agustin; Dhea Dinanty; M. Sawal Pitriyadi; Zulkarnain Abdurrahman; Tuti Anggraini (SEWAGATI: Jurnal Pengabdian Masyarakat Indonesia, 2025)
Financial education activities for Generation Z are crucial for fostering investment awareness from an early age. This article discusses the implementation of the Generation Z Financial Education outreach program: "Addressing Instant Solutions for a Sustainable Future," conducted by the UINSU FEBI Community Service Program (KKN) SMA at YPI Dharma Budi Private High School, Manik Maraja Village, Sidamanik District, Simalungun Regency, on August 26, 2025. A total of 120 12th-grade students actively and enthusiastically participated in this activity. Implementation methods included financial literacy outreach, interactive discussions, simple investment counseling, and the use of presentation media. Results showed that students showed high interest in investment topics, online loan risks, and personal financial planning. Barriers encountered included a lack of practical experience, a fear of risk, and a tendency toward a consumptive lifestyle. Nevertheless, this activity had a positive impact, increasing students' awareness of the importance of financial management, personal budgeting, and understanding that investing can be started with small capital. Thus, this financial education program plays a role in fostering a healthy, rational, and sustainable financial mindset for Generation Z.